Vitamin D Deficiency-A Public Health Issue in Children - Alexandru Herdea; Harun Marie; Adelina Ionescu; Diana-Mihaela Sandu; Sara-Teodora Pribeagu; Alexandru Ulici (MDPI AG, 2024)
Background: 25-hydroxyvitamin D [25(OH)D] deficiency is a global health concern, particularly in pediatric populations, with implications for musculoskeletal health and overall well-being. This study aimed to evaluate serum 25(OH)D levels in a pediatric population and assess the prevalence of deficiency and insufficiency. Methods: A retrospective analysis was conducted on data from 741 pediatric patients (2-17 years old) who visited an urban hospital for children for acute respiratory and gastrointestinal conditions in the span of 2 years. Serum 25(OH)D levels were measured using chemiluminescent microparticle immunoassay. Statistical analyses were performed to assess the prevalence of deficiency and insufficiency, seasonal variations, and correlations with age and daylight exposure. Results: Of the 739 pediatric patients analyzed, a substantial proportion exhibited insufficient (31.80%) or deficient (36.54%) serum 25(OH)D levels. While younger age groups generally had higher mean 25(OH)D levels, a negative correlation was observed between 25(OH)D levels and age. Sunlight exposure variations did not significantly impact serum 25(OH)D levels. Despite diverse daylight exposure patterns, there were no significant differences between longer and shorter daylight periods. Conclusions: This study highlights the high prevalence of 25(OH)D deficiency and insufficiency in the pediatric population, emphasizing the need for public health monitoring and targeted supplementation strategies. Findings underscore the importance of regular consultations with healthcare providers to ensure optimal 25(OH)D levels in children, with potential implications for revising current sufficiency thresholds. Addressing 25(OH)D deficiency is crucial for promoting musculoskeletal health and overall well-being in children.